(untitled) (International Journal of Agriculture and Sustainable Development, 2023)
This study presents a comprehensive analysis of major crop dynamics in Pakistan, focusing on cotton, sugarcane, rice, maize, and wheat, utilizing data from the Pakistan Bureau of Statistics. Despite the significant contributions of the agricultural sector to Pakistan’s economy, challenges such as population growth, decreasing per capita land availability, and fluctuations in crop production pose threats to sustainability. Through descriptive statistics and regression analysis, the study explores the relationships between crop production, GDP contribution, and agricultural value added. Cotton, sugarcane, rice, maize, and wheat collectively contribute to economic growth and food security, but their correlations with agricultural gain vary. While cotton and sugarcane exhibit low correlations, rice shows an inverse relationship, maize demonstrates a strong positive correlation, and wheat displays an insignificant correlation with agricultural gain. These findings underscore the complexity of Pakistan’s agricultural landscape, emphasizing the need for multifaceted strategies to enhance productivity, profitability, and sustainability in the sector.